Active Knee Rehabilitation Orthotic Device With Variable Damping Characteristics Implemented via an Electrorheological Fluid - Nikitczuk, Jason; Weinberg, Brian; Canavan, Paul K; Mavroidis, Constantinos (IEEE/ASME transactions on mechatronics, 2010)
This paper presents a novel, smart, and portable active knee rehabilitation orthotic device (AKROD) that provides variable damping at the knee joint, controlled in ways that can facilitate motor recovery in poststroke and other neurological disease patients, and to accelerate recovery in knee injury patients. The key features of AKROD include a compact, lightweight design, with highly tunable resistive torque capabilities through a variable damper component that is achieved through an electrorheological fluid (ERF) smart brake. Closed-loop torque and velocity controllers based on adaptive nonlinear control methodologies were developed and successfully implemented on the ERF brake. Preliminary testing of AKROD was performed using nine healthy subjects executing a set of isokinetic and isotonic exercises. These results were compared with exactly the same tests performed on a modern day computer controlled rehabilitation resistance machine, a Biodex System 3. The results showed comparable accuracy and repeatability between the two devices.